Benchmarking and Exploring Educational Tourism in Malaysia - Abid Nurhuda (Journal of English Language Teaching, Literature and Culture, 2023)
Malaysia is one of the countries that pay special attention to the tourism sector Its development is so rapid that modern places that so historically appear have their concepts and different characteristics ranging from buildings to magnificent urban areas that attract tourists to visit there including the UNU Surakarta Campus So the purpose of this study is to describe Benchmarking and Exploring Educational Tourism activities in Malaysia The method used is qualitative with a field study approach then the data is collected from 12 15 February 2023 followed by analyzing the contents and finally drawing conclusions The results of the study show that Benchmarking and Exploring Educational Tourism in Malaysia include four stages namely the preparation stage by formulating goals preparing plans and preparing the infrastructure then the socialization stage namely by discussing with students the rundown of the event how long it will be there and what matters only what must be prepared then the implementation stage is by visiting the Petronas Twin Towers Kuala Lumpur Indonesian School Genting Highland Christ Church Flor de la Mar Ship Universiti Melaka to the Putra Jaya Mosque And finally is the evaluation stage namely requiring students to compile reports in the form of scientific work < em>< p>